Development of an in Vitro System to Simulate the Adsorption of Self-Emulsifying Tea (Camellia oleifera) Seed Oil - Issara Sramala; Wichchunee Pinket; Pawinee Pongwan; Suwatchai Jarussophon; Kittiwut Kasemwong (Molecules, 2016)
In this study, tea (Camellia oleifera) seed oil was formulated into self-emulsifying oil formulations (SEOF) to enhance the aqueous dispersibility and intestinal retention to achieve higher bioavailability. Self-emulsifying tea seed oils were developed by using different concentrations of lecithin in combination with surfactant blends (Span®80 and Tween®80). The lecithin/surfactant systems were able to provide clear and stable liquid formulations. The SEOF were investigated for physicochemical properties including appearance, emulsion droplets size, PDI and zeta potential. The chemical compositions of tea seed oil and SEOF were compared using GC-MS techniques. In addition, the oil adsorption measurement on artificial membranes was performed using a Franz cell apparatus and colorimetric analysis. The microscopic structure of membranes was observed with scanning electron microscopy (SEM). After aqueous dilution with fed-state simulated gastric fluid (FeSSGF), the droplet size of all SEOF was close to 200 nm with low PDI values and the zeta potential was negative. GC-MS chromatograms revealed that the chemical compositions of SEOF were not significantly different from that of the original tea seed oil. The morphological study showed that only the SEOF could form film layers. The oil droplets were extracted both from membrane treated with tea seed oil and the SEOF in order to evaluate the chemical compositions by GC-MS.